An investigation into the characteristics of inertia gravity waves in the upper troposphere/lower stratosphere using a 205 MHz wind profiling radar. Issue 3 (4th March 2018) - Kottayil, Ajil; Satheesan, Karathazhiyath; Mohankumar, Kesavapillai; Chandran, Sivan; Samson, Titu
ABSTRACT: A stratosphere-troposphere (ST) wind profiler at 205 MHz is operational at the Advanced Centre for Atmospheric Radar Research (10.04 N; 76.33 E), Cochin University of Science and Technology, India. This profiler provides accurate three-dimensional wind profiles for an altitude range of 315 m to 20 km. In this paper, we present the characteristics of inertia-gravity waves (IGWs) observed in the upper troposphere/lower stratosphere from uninterrupted observations of wind profiles taken from 22–27 October 2016. The propagation properties of the waves were derived using hodograph analysis. The intrinsic period of the IGWs is found to be 28.75 hours, and the vertical and horizontal wavelengths of the wave are 3.74 and 1221 km, respectively. The hodograph shows a clockwise rotation of the ellipse, which indicates an upward propagation of energy from the upper troposphere to the lower stratosphere. These waves were observed in conjunction with a persistent deep depression over the Bay of Bengal.